An allocation analysis of Polish household savings invested in financial assets, 2003 - 2014 - Wiesław Dębski; Bartosz Świderski (Contemporary Economics, 2016)
This article addresses the allocation of Polish household savings that are invested in financial assets. As an economic category, these savings are very important in every country because they determine investments in the national economy, thereby influencing a country's further economic growth and development. From this point of view, investigating both the allocation of personal savings and their structure is essential because they change due to changing economic circumstances, changing situations in the world's financial markets, especially in the stock exchange markets, and the development of financial markets. The main purpose of this article is to analyze the changes in the allocation of savings in Polish households and the structure of their investment in financial assets. These changes, which are empirically observed, result from the circumstances of the national economy, which affect the behavior of investors in the stock market and determine the interest rate levels. The analysis is conducted on the basis of trend models with variations of parameters. The analysis has been carried out for the period Q4 2003 - Q3 2014.
Keywords: E20; G10; 330; savings of the Polish households; financial assets; analysis of allocation and its structure; trend models with variations of parameters